Identification of a PVL-negative SCCmec-IVa sublineage of the methicillin-resistant Staphylococcus aureus CC80 lineage: understanding the clonal origin of CA-MRSA. (March 2018) - Edslev, S.M.; Westh, H.; Andersen, P.S.; Skov, R.; Kobayashi, N.; Bartels, M.D.; Vandenesch, F.; Petersen, A.; Worning, P.; Larsen, A.R.; Stegger, M.
Abstract: Objectives: Community-acquired (CA) methicillin-resistant Staphylococcus aureus (MRSA) isolates belonging to clonal complex 80 (CC80) are recognized as the European CA-MRSA. The prevailing European CA-MRSA clone carries a type IVc staphylococcal cassette chromosome mec (SCC mec ) and expresses Panton-Valentine leukocidin (PVL). Recently, a significant increase of PVL-negative CC80 MRSA has been observed in Denmark. The aim of this study was to examine their genetics and epidemiology, and to compare them to the European CA-MRSA clone in order to understand the emergence of PVL-negative CC80 MRSA. Methods: Phylogenetic analysis of the CC80 S. aureus lineage was conducted from whole-genome sequences of 217 isolates (23 methicillin-susceptible S. aureus and 194 MRSA) from 22 countries. All isolates were further genetically characterized in regard to resistance determinants and PVL carriage, and epidemiologic data were obtained for selected isolates. Results: Phylogenetic analysis revealed the existence of three distinct clades of the CC80 lineage: (a) an methicillin-susceptible S. aureus clade encompassing Sub-Saharan African isolates ( n  = 13); (b) a derived clade encompassing the European CA-MRSA SCC mec -IVc clone ( n  = 185); and (c) a novel and genetically distinct clade encompassing MRSA SCC mec- IVa isolates ( n  = 19). All isolates in the novel clade were PVL negative, but carried remnant parts (8–12 kb) of the PVL-encoding prophage ΦSa2 and were susceptible to fusidic acid and kanamycin/amikacin. Geospatial mapping could link these isolates to regions in the Middle East, Asia and South Pacific. Conclusions: This study reports the emergence of a novel CC80 CA-MRSA sublineage, showing that the CC80 lineage is more diverse than previously assumed.